(untitled) (Andamios, Revista de Investigación Social, 2009)
Understanding democracy has raised a number of controversial issues and debates in political theory. Roughly, we can point out that democracy studies followed two different paths, i.e. understand democracy as a logic of social action or as a governmental mechanism to establish a governmental regime. From a post-structuralist theoretical perspective – under the aegis of the work of Chantal Mouffe and Jacques Rancière – this study try to develop across of the thesis about democracy with a critical approach to the rational –universal argument that built the relevance of liberal democracy. This type of analysis has the potential to resave the democratic paradox as a logic of social contigence.